SEMIOTIKA ROLAND BARTHES DALAM SYAIR “ASYIQ MIN FALISTHIN” KARYA MAHMUD DARWISH - Moh Ali Wafi; Irfan Effendi (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2023)
This study aims to describe the meaning by using Roland Barthes' semiotic theory in Mahmud Darwish's poem entitled " Asyiq min Falistin ". Barthes' theory consists of three systems of meaning, namely denotative meaning as the first order meaning, connotative meaning as the second order meaning, and the meaning of myth is the ideological operation of the meaning of connotation. The research methodology used is a descriptive qualitative methodology, this research examines objects in the form of poetry and examines them with Barthes theory and groups them to three systems of meaning. Using this methodology, an understanding of three semiotic systems of meaning is produced. In the meaning of denotation, we can see Mahmud Darwish's skill in choosing words that symbolize his longing, sadness and struggle for his motherland, Palestine. Then, from the connotation meaning, we can see more broadly how chaotic and full of suffering conditions were for the Palestinian people. So, the writer tried to fight even with many sacrifices. From the meaning of the myth, it can be seen from the perspective of how Palestine is defined as the "Holy Land".